Ajedrez como recurso didáctico para mejorar el aprendizaje significativo en el área de matemática de los niños de séptimo año de educación básica de la Escuela Gabriel Garcia Moreno de Urdaneta Parroquia Ricaurte - Merelo Sanchez, Irene Yolanda (2020)
Chess is a science, an art and a sport, which helps to develop: visual memory, combinatorial power, speed to calculate, concentration, logical thinking, creative thinking, improves cognitive abilities, mental speed, resolution of problems, logical-mathematical reasoning, among others. This research aims to implement chess as a recreational educational tool to help develop skills associated with the reasoning and acquisition of sequences in the students of the seventh year of basic education of the school "Gabriel García Moreno", through the analysis of utility and the benefits of chess as an educational tool. Like the effort, the game itself implies the mental effort to find new combinations, new paths. On the contrary, never underestimate the opponent, games are won or lost on the board. Courtesy, each game begins and ends with greetings. Self-improvement, always try to improve in the next game. Solidarity, the most prepared students help the least prepared. Mental order of reasoning and external order, placement of pieces and collection. New technologies and today's society increasingly lead to a lower capacity for attention and concentration, due in part to the large number of stimuli, the realization and depersonalization of interpersonal communications, individualism and loneliness. Instead, chess develops cognitive and social skills. It highlights twelve of them as the most relevant: It is one of the most popular games in the world is considered a mental sport.